Switching characteristic and analysis of insulated-gate bipolar transistor (IGBT) - Bakhtiar, Ahmad (2009)
Test circuit of Insulated-gate Bipolar Transistor (IGBT-type IRGPC50F); standard ultra fast speed IGBT will be operated when gate voltage, Vg is applied to the Gate-terminal. IR2109 (MOSFET/IGBT Driver) will amplify the pulse signal from function generator due to DC voltage supply input amplitude. Output of IR2109 connected to IGBT gate in the test circuit and the circuit operates. In the test circuit, IGBT will turn on ad off due to the input PWM signal from the driver circuit. The event of the switching on and off of the IGBT observe and the data note down. The factors affecting the switching mode discuss. Power dissipation and losses in the circuit calculated due to the test. The result is then compared to IGBT-type IRG4IBC20UDPBF; IGBT with ultra fast soft recovery diode. Analysis and conclusion then been made to compare the pros and cons between the 2 tested IGBT due on term of selectivity.